Characterising Mycobacterium tuberculosis Rv1510c protein and determining its sequences that specifically bind to two target cell lines (2005)
The process of Mycobacterium tuberculosis infection of the macrophage implies a very little-known initial recognition and adherence step, important for mycobacterial survival; many proteins even remain like hypothetical. The Rv1510c gene, encoding a putatively conserved membrane protein, was investigated by analysing the M. tuberculosis genome sequence data reported by Cole et al. and a previous report that used PCR assays to show that the Rv1510 gene was only present in M. tuberculosis. This article confirmed all the above and identified the transcribed gene in M. tuberculosis, Mycobacterium africanum, and in M. tuberculosis clinical isolates. Antibodies raised against peptides from this protein recognised a 44 kDa band, corresponding to Rv1510c theoretical mass (44,294 Da). Assays involving synthetic peptides covering the whole protein binding to U937 and A549 cell lines led to recognising five high activity binding peptides in the Rv1510 protein: 11094, 11095, 11105, 11108, and 11111. Their affinity constants and Hill coefficients were determined by using U937 cells. Cross-linking assays performed with some of these HABPs showed that they specifically bound to a U937 cell line 51 kDa protein, but not to Hep G2 or red blood cell proteins, showing this interaction’s specificity.